2007
DOI: 10.1021/ja075302g
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Coupled Folding of Cys2His2 Zinc-Finger

Abstract: Zinc-fingers, which widely exist in eukaryotic cell and play crucial roles in life processes, depend on the binding of zinc ion for their proper folding. To computationally study the zinc coupled folding of the zinc-fingers, charge transfer and metal induced protonation/deprotonation effects have to be considered. Here, by attempting to implicitly account for such effects in classical molecular dynamics and performing intensive simulations with explicit solvent for the peptides with and without zinc binding, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
123
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(133 citation statements)
references
References 74 publications
10
123
0
Order By: Relevance
“…Similarly, in BABZ7 and BABZ8, the mutations essentially destroyed the hydrophobic core. So the overall folding involves a delicate interplay of hydrophobic packing, hydrogen bonding, and metal binding (Li et al, 2007(Li et al, , 2008. In addition, if the coordination residues are located on flexible terminals or loops, as in BABZ2 and BABZ4, zinc binding-induced aggregation may occur, especially for the small protein like βαβ, so the entropy cost to fix the coordination residues at specific conformations should be considered, as zinc binding in proteins is an entropy-driven process (Reddi et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in BABZ7 and BABZ8, the mutations essentially destroyed the hydrophobic core. So the overall folding involves a delicate interplay of hydrophobic packing, hydrogen bonding, and metal binding (Li et al, 2007(Li et al, , 2008. In addition, if the coordination residues are located on flexible terminals or loops, as in BABZ2 and BABZ4, zinc binding-induced aggregation may occur, especially for the small protein like βαβ, so the entropy cost to fix the coordination residues at specific conformations should be considered, as zinc binding in proteins is an entropy-driven process (Reddi et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The metal ion induced protonation/deprotonation of ligand residues and the metal-induced polarization effect of the imidazole ring in the histidine residues were implemented by an empirical way (See ref. (165) for the the details). With these modifications, the metal coupled protein folding and other functional motions can be appropriately described by classical MD method.…”
Section: Metal-coupled Protein Foldingmentioning
confidence: 99%
“…These results again suggested that the Zn(II) is actively involved in the whole folding process, and its binding can direct and modulate the folding and stabilization of the secondary structures. Also, this crucial role of zinc binding is mediated by the packing of the conserved hydrophobic residues (165).…”
Section: Metal-coupled Protein Foldingmentioning
confidence: 99%
“…The computational simulations, on the other hand, might mimic and model this kind of interactions and avoid some complicated side effects. Molecular dynamics (MD) is one of these computational techniques, which is widely used in the studies of biomolecules [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55], and nanoscale systems [56][57][58][59][60]. It is found effective in providing insights to the interactions between proteins and CNTs.…”
Section: Introductionmentioning
confidence: 99%